Use of a mammography chamber in the characterization of radioprotection qualities N15 to N120 - LEONARDO CASTRO PACIFICO; José Guilherme Peixoto; Luis Alexandre Gonçalves (Brazilian Journal of Radiation Sciences, 2019)
The objective of the present work was to study the feasibility of the use of an ionization chamber dedicated to mammography in the characterization of radioprotection qualities referring to the series of narrow spectrum beams provided by ISO 4037-1. The results were satisfactory, and we conclude that it is feasible to use the ionization chamber dedicated to mammography to characterize the radiation protection qualities ISO-N15 to ISO-N120.